Analysis of the Caloric and Macronutrient Content of Meal Options Offered to Children at Popular Restaurant Chains - Deierlein, Andrea L.; Coffman, Kelley; Claudio, Luz (International Journal of Child Health and Nutrition, 2014)
Background: Previous research suggests that consumption of foods from restaurants is associated with poor dietary quality and adverse health outcomes. There are few studies that examine the nutrient content of children’s meal options offered at both sit-down and fast-food chain restaurants. The main objective was to describe the average energy and nutrient profiles of meal options on children’s menus at chain restaurants in the United States (US) and compare them to the Dietary Guidelines for Americans. Methods: The sample consisted of 13 sit-down and 16 fast-food restaurants ranked within the top 50 US restaurant chains in 2009 (meal nutrient content was accessed in 2010). There were 421 and 275 meal options listed on children’s menus from sit-down and fast-food restaurants, respectively. Descriptive statistics are presented for calories, fat, saturated fat, protein, carbohydrates, fiber, and sodium. Results: In general, nutrient contents of children’s meal options at sit-down and fast-food restaurants were similar. Meal options accounted for large percentages of the recommended daily intakes of calories, fat, saturated fat, and sodium and small percentages of the recommended daily intakes of fiber, carbohydrate, and protein for children. More than half of children’s meals at these restaurants exceeded recommendations for fat and saturated fat. Conclusions: Children’s meal options at sit-down and fast-food restaurant chains that complied with the US Dietary Guidelines were limited. The majority of the meal options had fat, saturated fat and sodium contents that exceed recommendations, while providing low amounts of fiber.